Credit Growth and Bank Soundness : Fast and Furious? - Igan, Deniz (IMF Working Papers; Working Paper, 2011)
We examine the risks to bank soundness associated with credit booms in a large set of countries. Using bank-level data in 90 countries between 1995 and 2005, we analyze the relationship between credit growth and bank soundness taking into account the potential two-way causality. We find that, while sounder banks tend to grow faster at moderate-growth periods, credit growth becomes less dependent on soundness during booms. These findings shed some light on why credit booms are often associated with financial crises.